The Existence of SMEs Business Performance During the Covid-19 Pandemic: Analyzing the Contribution of Intellectual Capital and Technological Innovation - Fedianty Augustinah; Erbin Chandra; Julyanthry Julyanthry; Debi Eka Putri; Acai Sudirman (Jurnal Organisasi dan Manajemen, 2022)
Purpose – The rapid and massive development of technology, information, and the internet in various business sectors, including SMEs, has created new changes. This situation provides opportunities and challenges for every business actors. Therefore, this study aims to analyze the effect of human, social, and customer capital, as well as technological innovation, on business performance. Methodology – The library and field design method were adopted with a quantitative approach, involving 180 samples of small and medium business actors. Furthermore, the Partial Least Square (PLS) was used to analyze the data. Findings – The result showed that human, social, and customer capital positively and significantly affected business performance. Similarly, technological innovation has a positive and significant impact on business performance. Originality – Employees who work in the small business sector will be relied upon in the future as agents of change. Many practitioners have expressed this in the field of human capital, which assumes greater responsibility for small company players in terms of the style of consultation.